Gestante con Placenta Previa Marginal - Casquete Cedeño, Ligia Mayly (2018)
In pregnancy, different pathologies may arise which, if not given due importance, may put at risk both the health of the mother and the baby. Placenta previa is currently affecting 1 in 200 pregnancies and is considered one of the main causes of hemorrhage during pregnancy, making it impossible for the mother to give birth through natural birth, and increasing the performance of a cesarean, the which unfortunately is related as one of the factors causing placenta previa. This case report concerns a 30-year-old patient with a pregnancy of 28 weeks of gestation, who presents with transvaginal bleeding of moderate amount and colicky pain, where she is admitted to the hospital unit to be under observation. The purpose of the application of the nursing care process is to provide comprehensive care to the patient, through the interventions given by the patient can improve their health status to achieve full maternal-fetal well-being.